Innovation of Transformative Islamic Education Strategy - Umam, Muhamad Khoirul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
The picture of the changing curriculum of education in Indonesia makes education less emphasize the religious character, lack of adaptation of science and technology of the future, influenced by global economic politics is accompanied by increasing education cost. The purpose of this study is to provide an overview of managing the skills and creativity of Islamic educational institutions as an effort to improve management development. So raises the question of research how innovative Islamic educational values ​​are integrated with transformative strategies to the needs of Islamic educational institutions of society?. To answer this research question, researchers collect data through the method of documentation-observation. Then after the data collected, analyzed through content analysis and critical analysis and synchronized with results of observation. So this study yields one of the proposed thoughts on innovation strategies that are expected to develop an integrative education with standards and figures of a sustainable future model